(untitled) - Duman, Tolga M. (Chichester, England ; Hoboken, NJ, 2007)
Coding for MIMO Communication Systems provides a complete overview of the various emerging space-time coding techniques. These include space-time trellis codes, space-time block codes, turbo codes, and concatenated codes with iterative decoding, among others. The book focuses on the construction and performance analysis of such coding schemes over various wireless channels. Comparisons between these coding schemes in terms of performance and complexity is also considered. A unified view of coding for MIMO systems is presented. The book also addresses information theoretical limits for multi-antenna systems over wireless channels. Furthermore, several practical space-time coding architectures such as BLAST and its variants are described. Other practical issues such as antenna selection at the transmitter and/or receiver and the effects of sub-channel correlation on the system performance are also considered
Keywords: Space time codes,MIMO systems,Wireless communication systems; Hệ thống MIMO,Truyền thông không dây